STRATEGIES TO IMPROVE STUDENTS’ DIGITAL LITERACY IN HIGHER EDUCATION - Khamdamov , Nozimjon Nurdinbekovich (Educational Research in Universal Sciences, 2024)
Digital literacy has become a critical skill for students in the 21st century, as they navigate an increasingly technology-driven academic and professional landscape. This research paper examines effective strategies for enhancing digital literacy among university students. Drawing on a comprehensive review of the literature and empirical studies, the paper identifies key components of digital literacy, including information management, digital communication, content creation, and problem-solving. It then presents a multi-pronged approach to improving students’ digital literacy, encompassing curriculum integration, faculty development, and student-centered learning initiatives. The findings highlight the importance of a holistic, institution-wide effort to foster digital literacy, as well as the need for continuous evaluation and adaptation of these strategies to meet the evolving needs of the digital age.